The analysis of struck-by accidents at construction sites in Johor - Abas, Nor Haslinda; Yap, Wai Heong; Mohammad, Hairuddin; Yaman, Siti Khalijah; Rahmat, Muhamad Hanafi (Penerbit UTHM, 2020)
Malaysia’s construction industry has been categorized as the most hazardous industry due to its high risk in causing construction accidents compared to the other industry. Among the various reported accident fatality cases to the Department of Occupational Safety and Health (DOSH) from the year 2010 to 2018, ‘struck-by object’ is among the most accounted fatal accident types. This study aims to analyse the struck-by accidents at construction sites in Johor and investigate the significant contributing factors of this type of accident. It was carried out by computing the contributing factors of struck-by accidents from the DOSH website, which was later designed as questionnaire questions. The questionnaire was distributed to 150 respondents that comprise of safety personnel who are working at construction sites, and about 116 answered questionnaires were received. From the questionnaire survey, the most significant contributing factor to struck-by object accidents is due to lack of training. Whereas for the analysis of the real cases, the significant contributing factor to struck-by object accidents is due to inadequate safe operating procedures. Using Spearman’s rank correlation, it was found that there is a variation in the respondents’ perceptions with the real fatal cases reported in the DOSH website. This results from this study create major eye-opening on the weak correlational relationship between the safety personnel’s perceptions and what actually the cause is. This study provides awareness on the issue and further actions should be taken to ensure the fatality rate of struck-by object accidents could be reduced.